Responsible Public Management : Communicative Assessment of Administrative Doctrines - Autioniemi, Jari (Vaasan yliopisto, 2021)
This thesis assesses forms of responsibility through the theory of communicative action by Jürgen Habermas. In the study, the administrative doctrines are represented by bureaucratic theory, New Public Management (NPM) and New Public Governance (NPG). The study is based upon abductive content analysis and a narrative literature review. The study provides an opportunity to understand what practical organizational and management arrangements are required to implement and support responsibility. Research in the topic is needed since governance indices indicate that, despite administrative reforms through decades, public trust in governments has not risen. Whereas bureaucratic theory emphasizes compliance-based responsibility, NPM high-lights the need for assessing accountability in terms of results and NPG accountability in networks. The administrative doctrines open up the issue of responsibility in different ways since they describe technical rationality from different perspectives. The quest for greater efficiency, economy and effectiveness in public administration has given rise to new forms of responsibility, which both complement and complicate previous forms of organisatory arrangements. Results indicate a paradoxical image of responsible public management. Hence, more research is needed to assess the impact of administrative reforms on administrative ethics.
Keywords: public administration; liability; ethics; administration (systems of a society); communication; bureaucracy; responsibility (properties); leadership (activity); evaluation; rationality; fi=Julkisjohtaminen|en=Public Management|